2006
DOI: 10.3171/jns.2006.105.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery for metastatic brainstem tumors

Abstract: Compared with allowing a metastatic brainstem lesion to take its natural course, GKS prolongs survival. The risks associated with such treatment are low. The severity of systemic diseases largely determines the prognosis of metastases to the brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 32 publications
5
64
2
1
Order By: Relevance
“…16,17 All of these studies have shown that SRS is a safe, reliable, and efficient treatment method for brainstem metastases. [3][4][5][6][13][14][15][16][17] This study differs from others in reporting treatment results of not only metastases in the brainstem but also those that are adjacent to brainstem (≤5 mm) and using CyberKnife as an FSRT/ SRS system. The CyberKnife SRT system has certain improved features of utility compared to the Gamma Knife radiosurgery system.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…16,17 All of these studies have shown that SRS is a safe, reliable, and efficient treatment method for brainstem metastases. [3][4][5][6][13][14][15][16][17] This study differs from others in reporting treatment results of not only metastases in the brainstem but also those that are adjacent to brainstem (≤5 mm) and using CyberKnife as an FSRT/ SRS system. The CyberKnife SRT system has certain improved features of utility compared to the Gamma Knife radiosurgery system.…”
Section: Discussioncontrasting
confidence: 49%
“…In the current literature, most of the studies have used Gamma Knife for the treatment of brainstem metastases using stereotactic radiosurgery. 3,5,6,[13][14][15] In addition, there are other studies in which linac-based systems were used as a means of SRS. 16,17 All of these studies have shown that SRS is a safe, reliable, and efficient treatment method for brainstem metastases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations